The effect of caffeine as an ergogenic aid in anaerobic exercise - Woolf, K.; Bidwell, W. D.; Carlson, A. G. (International Journal of Sport Nutrition and Exercise Metabolism, 2008)
The study examined caffeine (5 mg/kg body weight) vs. placebo during anaerobic exercise. Eighteen male athletes (24.1 ± 5.8 yr; BMI 26.4 ± 2.2 kg/m2) completed a leg press, chest press, and Wingate test. During the caffeine trial, more total weight was lifted with the chest press, and a greater peak power was obtained during the Wingate test. No differences were observed between treatments for the leg press and average power, minimum power, and power drop (Wingate test). There was a significant treatment main effect found for postexercise glucose and insulin concentrations; higher concentrations were found in the caffeine trial. A significant interaction effect (treatment and time) was found for cortisol and glucose concentrations; both increased with caffeine and decreased with placebo. Postexercise systolic blood pressure was significantly higher during the caffeine trial. No differences were found between treatments for serum free-fatty-acid concentrations, plasma lactate concentrations, serum cortisol concentrations, heart rate, and rating of perceived exertion. Thus, a moderate dose of caffeine resulted in more total weight lifted for the chest press and a greater peak power attained during the Wingate test in competitive athletes.